Morphometry of network and nonnetwork space of basins - Chockalingam, L. (2005)
[1] Morphometric analysis of channel network of a basin provides several scale-independent measures. To better characterize basin morphology, one requires, besides channel morphometric properties, scale-independent but shape-dependent measures to record the sensitive differences in the morphological organization of nonnetwork spaces. These spaces are planar forms of hillslopes or the retained portion after subtracting the channel network from the basin space. The principal aim of this paper is to focus on explaining the importance of alternative scale-independent but shape-dependent measures of nonnetwork spaces of basins. Toward this goal, we explore how mathematical morphology-based decomposition procedures can be used to derive basic measures required to quantify estimates, such as dimensionless power laws, that are useful to express the importance of characteristics of nonnetwork spaces via decomposition rules. We demonstrate our results through characterization of nonnetwork spaces of eight subbasins of the Gunung Ledang region of peninsular Malaysia. We decompose the nonnetwork spaces of eight fourth-order basins in a two-dimensional discrete space into simple nonoverlapping disks (NODs) of various sizes by employing morphological transformations. Furthermore, we show relationships between the dimensions estimated via morphometries of the network and their corresponding nonnetwork spaces. This study can be extended to characterize hillslope morphologies, where decomposition of three-dimensional hillslopes needs to be addressed.